German female rap: Crisis management of socially disadvantaged female adolescents - Yesilbas, Filiz D; Witte, Matthias D (American Journal of Social Sciences and Humanities, 2025)
Adolescence is a period of crisis in which young people cope with identity, insecurity, and orientation problems. The musical genre known as German Female Rap represents a medium of expression and distinction for establishing an identity that offers young listeners the scope to seek orientation. For some years now, women artists have been pursuing female self-empowerment by successfully rapping about issues such as sexuality, gender, body positivity, emotions, and ethnicity. Our explorative study is based on the findings of a research project conducted in Germany in 2022. We analyzed 20 song lyrics by female artists and eight guided interviews with young people and discuss how socially disadvantaged adolescent females establish agency in age-specific crises through Female Rap. All interviewees were adolescents between the ages of 14 and 19 with a post-migrant history. Encouraged by songs and protagonists, these young female listeners experience themselves as self-empowered actors with new ideas about self-presentation. However, identification with idols can also lead to stigmatization and exclusion. Appropriation between mimetic isomorphism and autonomous positioning should be considered as an actor-specific coping strategy during the adolescent crisis phase. For practical youth work, this study points to the high significance of informal fields of socialization beyond the limits of pedagogical settings.